Immune response induced by oral delivery of Bacillus subtilis spores expressing enolase of Clonorchis sinensis in grass carps (Ctenopharyngodon idellus). Issue 60 (January 2017) - Jiang, Hongye; Chen, Tingjin; Sun, Hengchang; Tang, Zeli; Yu, Jinyun; Lin, Zhipeng; Ren, Pengli; Zhou, Xinyi; Huang, Yan; Li, Xuerong; Yu, Xinbing
Abstract: Clonorchiasis, caused by the consumption of raw or undercooked freshwater fish containing infective metacercariae of Clonorchis sinensis is ( C.sinensis ), remains a common public health problem. New effective prevention strategies are still urgent to control this food-borne infectious disease. The previous studies suggested Bacillus subtilis ( B. subtilis ) spores was an ideal vaccines delivery system, and the C.sinensis enolase ( Cs ENO) was a potential vaccine candidate against clonorchiasis. In the current study, we detected Cs ENO-specific IgM levels by ELISA in sera, intestinal mucus and skin mucus in grass carps ( Ctenopharyngodon idella ) through oral administration with B. subtilis spores surface expressing Cs ENO. In addition, immune-related genes expression was also measured by qRT-PCR. Grass carps orally treated with B. subtilis spores or normal forages were used as controls. The results of ELISA manifested that specific IgM levels of grass carps in Cs ENO group in sera, intestine mucus and skin mucus almost significantly increased from week 4 post the first oral administration when compared to the two control groups. The levels of specific IgM reached its peak in intestine mucus firstly, then in sera, and last in skin mucus. qRT-PCR results showed that 5 immune-related genes expression had different degree of rising trend in Cs ENO group when compared to the two control groups. Our study demonstrated that orally administrated with B. subtilis spores expressing Cs ENO induced innate and adaptive immunity, systemic and local mucosal immunity, and humoral and cellular immunity. Our work may pave the way to clarify the exact mechanisms of protective efficacy elicited by B. subtilis spores expressing Cs ENO and provide new ideas for vaccine development against C. sinensis infection. Highlights: Apply Bacillus subtilis spores as delivery system to fish for the first time. Focus on freshwater fish to prevent clonorchiasis for the first time. Preliminary clarify immunological mechanism of the recombinant spores. Provide a new idea about cutting off the spreading approach of clonorchiosis.